Perception and User Satisfaction on Interior Design of Fadel Muhammad Resources Center (FMRC) - Lastiti Veri Anggaini, Niken (Jurnal Ilmiah Administrasi Publik, 2019)
User satisfaction can be measured one through the interior design, as the interior design is part of supporting the convenience that must be considered in the library. A good library’s interior design will create the impression of comfort and satisfaction to user. This research used quantitative descriptive research with used design interior and user satisfaction concept. It consists of several variables, i.e. space, color, lighting, air circulation, sound, as well as satisfaction. Measurement scale used is Likert scale with a sample of 110 respondents. Results of the study showed that Perception and User Satisfaction of FMRC interior Design can be seen detailed from space variable with a grand mean score (3.32), color variable (3.36), lighting variable (3.31), air circulation variable 3,48), sound variable (3.34), andconvenience variables (3.62). It means that perception and user satisfaction of space, color, lighting, and sound variable are included in medium category while air circulation and convenience variable are included in high category.